Character Education and Friendship on Students’ Self-Esteem - Sugiarti, Rini; Erlangga, Erwin; Purwaningtyastuti, Purwaningtyastuti; Wisudaningtyas, Adisty (Journal of Nonformal Education, 2022)
This study aimed to demonstrate that character education and friendship are factors that influence or foster self-esteem in adolescents. To validate the statement, 250 students in Semarang participated and are involved in this study. Three hypotheses were formulated and tested. The major hypothesis was that character education and friendship have an effect on self-esteem in adolescents. The first minor hypothesis was that character education has an effect on students’ self esteem and the second minor hypothesis was that friendship has an effect on self-esteem in adolescents. The results of data analysis show that all hypotheses are accepted. Furthermore, based on the results, the researchers suggested that character education and friendship dimensions should be considered in an intervention program intended to promote the potential of education character and friendship as a means of fostering self-esteem in adolescents as a foundation for growth and development in the future.